Anthropometric indices and physical activity in relation to premenstrual syndrome among female adolescents - Maulidiana, Annisa Rizky; Qomariah, Putri Nabila; Rahmawati, Savitri Nur; Airin, Airin; Nazifa, Azzahra; Nurazizah, Dumay Mutiara; Chrishargyantari, Tirsa Dewanti; Ventiyaningsih, Agustiana Dwi Indiah; Fahmi, Ilmia (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Premenstrual syndrome (PMS) is a collection of symptoms that are usually experienced by female adolescent before the start of each menstrual cycle which can impact their social activities and concentration on studies. There are several factors that can influence the occurrence of PMS, such as nutritional status, body composition, and physical level.  Objectives: To explore the incidence of PMS among female adolescents and its correlation with anthropometric indices and physical activity in Malang City, IndonesiaMaterials and Methods: A cross-sectional study was conducted in August to November 2023. A total of 143 female second year students from three public high schools in Malang City was participated in this study. Weight, height, waist circumference, hip circumference, and body fat percentage (BF%) were measured. Anthropometric indices including body mass index-for-age (BMI-for-age), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR) were calculated. PMS was measured using 10-item shortened Premenstrual Assessment Form(sPAF) and physical activity using Physical Activity Questionnaire for Adolescent (PAQ-A). Spearman test was used to evaluate the correlation between variables.Results: There were significant positive correlations among anthropometric indices. There was a positive correlation between PMS with BF%, WHR, and WHtR, however no correlation was found with BMI-for-age. PMS was inversely correlated with physical activity level.Conclusion: Anthropometric indices as predictor of obesity such as BF%, WHR, and WHtR was positively correlated with PMS while physical activity was negatively correlated with PMS. These findings suggest that changes toward healthy lifestyle, such as having regular physical activity and maintain a normal range of body composition and nutritional status are important to alleviate PMS symptoms in female adolescents.Keywords: Adolescent; anthropometric indices; body fat; physical activity; premenstrual syndrome